PENGARUH BEBERAPA SPESIES FUNGI MIKORIZA ARBUSKULAR TERHADAP PERTUMBUHAN BIBIT PINANG HUTAN (Areca catechu L.) - Yuliati, Ira Yuliati; Yusran, Yusran; Irmasari, Irmasari (Jurnal Warta Rimba, 2015)
Areca catechu L. is one the member of Palmae family that grow widely in Pacific, Asia and East Africa. Seed propose marriage to obtained from betelnut which have [in] paring. Seed propose marriage to known as by one of mixture eat the a kind of plant. Others, Seed of good for food-stuff, industrial raw material like cloth colourant, and medicinize. Like also frond propose marriage to the, seed even also need the processing to get the the product. Seed propose marriage to this exploited by as drug, worm drug, eczema, toothache, flu, hurt, scabies, difteri, menstrual pain in bone, nosebleed, sprue, mencret, scabby, ulcer. A study on the effects of some arbuscular mycorrhizal fungi (AMF) species on the growth of Areca catechu L. seedlings was conducted at the greenhouse of Forestry Faculty, Tadulako University, Central Sulawesi. The research was conducted from Pebruary to May 2014.The experiment was laid out in a Randomized Complete Design (RCD) with four treatments;without mycorrhizal inoculation/control (M0), Glomus mosseae (M1), Glomus etunicatum (M2) and Glomus clorum (M3). Five replication of each treatment combination was used for this study. Observation Parameters consist of seedling height increment, stem diameter increment, and increment of leaf number per plant. The results showed that treatments of FMA species had significant effect on the seedling height increment, stem diameter increment and increment of leaf number per plant. Better A. catechu seedlings growth was achieved by both AMF species treatments compared to control treatments. Therefore, both AMF species are recommended for bio-fertilizer at nursery stage of A. catechu L. Keywords: Arbuscular Mycorrhizal Fungi, Seedling growth, Areca catechu L.